A New Endemic Mimosa (Leguminosae, Mimosoideae) from Pampa Biome, Brazil - Silveira, Fernanda Schmidt; Bordignon, Sérgio; Miotto, Silvia Teresinha Sfoggia (Phytotaxa, 2016)
Mimosa terribilis (Leguminosae, Mimosoideae), a new subshrub species, endemic from Pampa grasslands of Rio Grande do Sul State in Southern Brazil, is described and illustrated. The new species is morphologically close to Mimosa ramosissima with respect to its subshrub habit, recurved aculei, stipules 1-nerved, calyx narrowly campanulate, inflorescence capituliform and globose, besides hispid pods. The new species differs from M. ramosissima by not being lobate calyx, nor having nervate calyx; having indumentum that is only puberulent and shorter peduncles (3–6mm long). Furthermore, this species has a narrowly distribution, being known only for south of Rio Grande do Sul State while M.ramosissima is distributed along south and southeast of Brazil.